(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the shifting landscape of higher education, emotional well-being has emerged as a silent architect behind academic success. This study delves into the intricate psychological dimensions-status, situation, self-awareness, and power/resilience-shaping university students’ academic performance. Utilizing the Socio-Emotional Well-Being Index (SEWBI) across 480 students in Haryana’s Rohtak and Jhajjar districts, the research reveals a moderate yet meaningful positive correlation between emotional health and academic outcomes (r = 0.2961, p < 0.001). Notably, self-awareness and psychological resilience surfaced as the most influential emotional traits linked to higher academic achievement. Gender, academic level (UG/PG), and rural–urban residential background were found to have no significant bearing on emotional well-being, while academic stream significantly impacted self-awareness (p = 0.0183). Though regression analysis fell just short of statistical significance (p = 0.0634), the directional trend underscored emotional stability as a positive predictor of academic performance. This study positions emotional well-being not as an auxiliary concern but as a core academic variable, urging institutions to embed emotional intelligence, mindfulness, and resilience training within curricular and policy frameworks. Fostering emotionally aware and balanced students is no longer optional; it is essential for educational excellence.